Development of Sparcol Videoscribe-Based Video Media in Thematic Learning - Alfiyandri Alfiyandri; Riri Marfilinda; Amelia Annisa Fitri; Fadhilah Al Humaira (Postgraduate, University of Mataram, 2023)
This research is motivated by the integrated thematic learning media used in elementary schools that are not yet technology-based and designed as attractive as possible. This study aims to develop a learning media based on Sparkol Videoscribe in integrated thematic learning in class V SD that is valid, practical and effective. This research is development research (R&D) with the Plomp development model. The Plomp development model consists of three phases: the preliminary research phase, the development or prototyping phase, and the assessment phase. The results of this study indicate that the learning media developed have a level of validity, namely: design experts 95.8%, linguists 89.2% and (3) material experts 90.6%. Practicality level, from students 94.2% and teacher practicality 91.6%. The results of the effectiveness of learning media show effective results on student learning outcomes. It is known from the comparison of the average posttest results of students and the hypothesis testing of the posttest results which are higher than the pretest results. Posttest results show an average of 85%, while pretest results show an average of 67% (quite effective). Meanwhile, the hypothesis test showed Pvalue â‰¤ Î± (0.002â‰¤0.05).